Construction of 3D Volumetric Objects for a 3D Cadastral System. Issue 5 (25th November 2014) - Ying, Shen; Guo, Renzhong; Li, Lin; Van Oosterom, Peter; Stoter, Jantien
Abstract This article presents a new method to illustrate the feasibility of 3D topology creation. We base the 3D construction process on testing real cases of implementation of 3D parcels construction in a 3D cadastral system. With the utilization and development of dense urban space, true 3D geometric volume primitives are needed to represent 3D parcels with the adjacency and incidence relationship. We present an effective straightforward approach to identifying and constructing the valid volumetric cadastral object from the given faces, and build the topological relationships among 3D cadastral objects on‐the‐fly, based on input consisting of loose boundary 3D faces made by surveyors. This is drastically different from most existing methods, which focus on the validation of single volumetric objects after the assumption of the object's creation. Existing methods do not support the needed types of geometry/topology (e.g. non 2‐manifold, singularities) and how to create and maintain valid 3D parcels is still a challenge in practice. We will show that the method does not change the faces themselves and faces in a given input are independently specified. Various volumetric objects, including non‐manifold 3D cadastral objects (legal spaces), can be constructed correctly by this method, as will be shown from the results.